A preliminary study of the genus Nymphicula Snellen from Australia, New Guinea and the south Pacific (Lepidoptera: Pyraloidea: Crambidae: Acentropinae) - Agassiz, David (Zootaxa, 2014)
The species of Nymphicula occurring in Australia and south Pacific islands are described and illustrated. 22 new species are described: N. adelphalis, N. christinae, N. conjunctalis, N. edwardsi, N. hampsoni, N. ochrepunctalis, N. torresalis, N. beni, N. irianalis, N. michaeli, N. monticola, N. nokensis, N. plumbilinealis, N. submarginalis, N. susannae, N. tariensis, N. xanthocostalis, N. fionae, N. insulalis, N. lactealis, N. lifuensis, N. cheesmanae. A replacement name is proposed for Cataclysta dialitha Tams: Nymphicula samoensis.